Galectin‐9 mediates neutrophil capture and adhesion in a CD44 and β2 integrin‐dependent manner. Issue 1 (30th November 2021) - Iqbal, Asif J.; Krautter, Franziska; Blacksell, Isobel A.; Wright, Rachael D.; Austin‐Williams, Shani N.; Voisin, Mathieu‐Benoit; Hussain, Mohammed T.; Law, Hannah L.; Niki, Toshiro; Hirashima, Mitsuomi; Bombardieri, Michele; Pitzalis, Costantino; et al.
Abstract: Neutrophil trafficking is a key component of the inflammatory response. Here, we have investigated the role of the immunomodulatory lectin Galectin‐9 (Gal‐9) on neutrophil recruitment. Our data indicate that Gal‐9 is upregulated in the inflamed vasculature of RA synovial biopsies and report the release of Gal‐9 into the extracellular environment following endothelial cell activation. siRNA knockdown of endothelial Gal‐9 resulted in reduced neutrophil adhesion and neutrophil recruitment was significantly reduced in Gal‐9 knockout mice in a model of zymosan‐induced peritonitis. We also provide evidence for Gal‐9 binding sites on human neutrophils; Gal‐9 binding induced neutrophil activation (increased expression of β2 integrins and reduced expression of CD62L). Intra‐vital microscopy confirmed a pro‐recruitment role for Gal‐9, with increased numbers of transmigrated neutrophils following Gal‐9 administration. We studied the role of both soluble and immobilized Gal‐9 on human neutrophil recruitment. Soluble Gal‐9 significantly strengthened the interaction between neutrophils and the endothelium and inhibited neutrophil crawling on ICAM‐1. When immobilized, Gal‐9 functioned as an adhesion molecule and captured neutrophils from the flow. Neutrophils adherent to Gal‐9 exhibited a spread/activated phenotype that was inhibited by CD18 and CD44 neutralizing antibodies, suggesting a role for these molecules in the pro‐adhesive effects of Gal‐9. Our data indicate that Gal‐9 is expressed and released by the activated endothelium and functions both in soluble form and when immobilized as a neutrophil adhesion molecule. This study paves the way for further investigation of the role of Gal‐9 in leukocyte recruitment in different inflammatory settings.